2020
DOI: 10.21873/cgp.20178
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association Between the MiR146a Genotypes and Susceptibility to Childhood Acute Lymphoblastic Leukemia in Taiwan

Abstract: Background/Aim: Mounting evidence has shown that miRNAs play a critical role in the regulation of hematopoiesis of cell proliferation and apoptosis as well as in tumorigenesis. The miR146a rs2910164 polymorphism, which is closely responsive for its expression, has been reported to associate with the risk of several solid cancers. The study aimed at examining the association of the it with susceptibility to childhood acute lymphoblastic leukemia (ALL) in Taiwan. Materials and Methods: We recruited 266 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Oral cancer IL-16 genotyping methodology. Genomic DNA from the peripheral blood leucocytes of all oral cancer patients and matched controls were extracted using the QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and further processed in typical polymerase chain reaction (PCR) processes as in our previous papers (20)(21)(22). The sequences of designed forward and reverse primers, corresponding restriction enzymes (New England BioLabs, Ipswich, MA, USA) and sizes of PCR products after enzyme digestion for oral cancer IL-16 genotyping identification are shown in Table II.…”
Section: Methodsmentioning
confidence: 99%
“…Oral cancer IL-16 genotyping methodology. Genomic DNA from the peripheral blood leucocytes of all oral cancer patients and matched controls were extracted using the QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and further processed in typical polymerase chain reaction (PCR) processes as in our previous papers (20)(21)(22). The sequences of designed forward and reverse primers, corresponding restriction enzymes (New England BioLabs, Ipswich, MA, USA) and sizes of PCR products after enzyme digestion for oral cancer IL-16 genotyping identification are shown in Table II.…”
Section: Methodsmentioning
confidence: 99%
“…A significant association of miR-146a rs2910164 with childhood ALL has been reported in an Iranian population (Hasani et al, 2014 ). This result was successfully replicated in two Chinese case-control studies (Liu et al, 2018 ; Pei et al, 2020 ). In contrast, three studies from Thailand, India and China failed to replicate the results (Chansing et al, 2016 ; Devanandan et al, 2019 ; Xue et al, 2019 ).…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies found that the rs2910164 CC or CG genotype significantly increased the risk of ALL (Hasani et al, 2014 ; Liu et al, 2018 ). The miR146a rs2910164 GG genotype was significantly related to a decreased susceptibility to childhood ALL (Pei et al, 2020 ). This study confirms that the miR146a rs2910164 polymorphism (G>C) contributes to childhood ALL susceptibility among Asians.…”
Section: Discussionmentioning
confidence: 99%
“…CCND1 rs9344 and rs678653 genotyping procedures. Genomic DNA was extracted from each person's peripheral blood leukocytes within 24 h after collection, carefully quantitated, diluted, and stored in a −80˚C freezer as previously described (25)(26)(27). The genotypic patterns at CCND1 rs9344 were determined for all subjects by typical polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis as in our previous publications (28,29).…”
Section: Recruitment Of Participants Into Asthmatic and Non-asthmatic Control Groupsmentioning
confidence: 99%